1998
DOI: 10.3758/bf03206037
|View full text |Cite
|
Sign up to set email alerts
|

The role of head-centric spatial reference with a static and kinetic visual disturbance

Abstract: A static or kinetic visual disturbance affects subjects' ability to estimate the direction of the gravitational vertical. This kind of error is increased by a head roll inclination. In two experiments, we combined head orientation with a static (Experiment 1: tilted frame) versus kinetic (Experiment 2: rotating disk) visual disturbance. The results showed that with a static visual disturbance, the increase of errors in the inclined head condition was mainly the consequence of a postural head effect like an Aub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
26
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 28 publications
5
26
0
3
Order By: Relevance
“…Using high-density 192-channel EEG it was possible to record brain activity and performance in VV judgments in an ecologically valid situation (upright body axis aligned with gravity) whereas the VV judgements. Our behavioral data also revealed that the VV was significantly deviated towards the tilted visual references in the RFT, thus confirming previous observations in healthy populations (Guerraz et al, 1998;Lopez et al, 2006;Marendaz, 1998;Witkin and Asch, 1948;Zoccolotti et al, 1992). These effects were absent in the control task.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using high-density 192-channel EEG it was possible to record brain activity and performance in VV judgments in an ecologically valid situation (upright body axis aligned with gravity) whereas the VV judgements. Our behavioral data also revealed that the VV was significantly deviated towards the tilted visual references in the RFT, thus confirming previous observations in healthy populations (Guerraz et al, 1998;Lopez et al, 2006;Marendaz, 1998;Witkin and Asch, 1948;Zoccolotti et al, 1992). These effects were absent in the control task.…”
Section: Discussionsupporting
confidence: 91%
“…The role of vestibular and somatosensory cues in VV judgments was confirmed in participants rotated in their frontal plane and committing VV judgments errors whose amplitude and direction depended on the amount of body tilt (Kaptein and Van Gisbergen, 2004;Mittelstaedt, 1983;Van Beuzekom and Van Gisbergen, 2000;Van Beuzekom et al, 2001;Vingerhoets et al, 2009). Finally, the importance of visual cues has been demonstrated by the large deviations of the VV evoked by optic flow rotating around the line of sight (Dichgans et al, 1972;Guerraz et al, 1998;Lopez et al, 2007) and oriented visual environments (Dyde et al, 2006). In the widely used and validated 'rod and frame test' (RFT) participants are required to judge the orientation of a mobile rod that is embedded in a tilted square frame (Witkin and Asch, 1948).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The concept of visual dependence derives from the fact that spatial orientation is based on both vestibuleproprioceptive and visual cues and that nondisabled people make variable and idiosyncratic use of such cues for spatial orientation [11,14,28] and postural control [29]. It has been suggested that such perceptual preferences observed in nondisabled people are also present, if not enhanced, in patients with a balance disorder [11] and in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular, visual, and somatosensory information all contribute to this perception. 1,2 Assessment of the verticality of the environment in the upright position needs mainly vestibular and visual inputs. Somatosensory information is required when the head or the whole body is tilted.…”
mentioning
confidence: 99%